An Overview of Rate of Infection and Mortality in Femur Fracture Patients and its Fixation during Covid-19 Pandemic - Muhammad Ali Ayub, Ali Ijaz Ahmad, Hizbullah Riaz Ansari, Mohammad Omar Aziz, Rizwan Akram, Amer Aziz, Ashfaq Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To observe the workload of fractures of the femur (shaft and distal femur) and their fixations along with complications in terms of infection and mortality at our hospital during COVID 19 pandemic. Study design: Prospective study. Place and duration of study: Dept of Orthopaedic, Ghurki Trust Teaching Hospital, Lahore from 01-03-2020 to 31-07-2020 Methodology: One hundred and thirty-one diagnosed patients with femur fracture (shaft and distal) during pandemic period of COVID were enrolled. Demographic data included (age, sex, implant type, surgical site infection (SSI) and mortality).Since study was done during COVID-19 pandemic, positivity of COVID symptoms was noted as yes/ no on data collection proforma. Results: There were 105 (80.15%) males while 26 (19.84%) were females with mean age was 39.20±13.02 years. Majority of the surgical interventions were done based on Intramedullary nailing 74.05%, the second prevalent surgeries were done on AO external fixation 8.4%. Infection rate was observed in 7(5.32%) patients. No mortality was seen in any of the cases. Four infected cases were observed after intramedullary nailing procedure, two from AO external fixation and one after locking plate. Conclusion: There is no significant higher complication rate due to COVID-19 pandemic to patients whom femur fracture fixation was done. None of admitted patient suffered COVID-19 symptoms during hospitalization. It was only pointless fear about orthopaedic intervention during this interval.